Diskresi Pemerintah Daerah Dalam Penetapan Tarif Pajak Hiburan Pasca Implementasi Undang-Undang Nomor 1 Tahun 2022 Tentang Hubungan Keuangan Antara Pemerintah Pusat dan Pemerintah Daerah - Ayuningtyas Manggiasih, Rahajeng (Universitas Ekasakti, 2024)
The implementation of Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments (UU HKPD) has changed the structure and tax rates at the regional level, particularly for Specific Goods and Services Tax (PBJT) on arts and entertainment services. These changes include adjustments to entertainment tax rates, which are now set at a minimum of 40% and a maximum of 75% for specific entertainment services such as discotheques, karaoke, nightclubs, bars, and steam baths/spas. Although the increase in rates is in accordance with the provisions of UU HKPD, the policy has sparked controversy and widespread opposition, especially from entertainment business operators who are just beginning to recover post-COVID-19 pandemic. The determination of the PBJT rates is carried out by local governments through Regional Regulations as an implementation of UU HKPD. Local governments are expected to utilize the discretion provided by the law to set tax rates that not only increase regional revenue but also support the growth of the local entertainment industry.